2010
DOI: 10.1007/bf03262758
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Rehabilitation of a child with dentinogenesis imperfecta and congenitally missing lateral incisors

Abstract: This case illustrates the need for appropriate and timely restorative treatment to prevent deterioration of the dentition. This case will also demonstrate that low-fusion metal ceramic restoration is a viable esthetic treatment option for today's patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…We have treated other cases without complications after 10 years or more. 25,33,34 Urzua et al reported a case of hypocalcified AI rehabilitated with 28 ceramic metal-free…”
Section: Prosthodontic Proceduresmentioning
confidence: 99%
“…We have treated other cases without complications after 10 years or more. 25,33,34 Urzua et al reported a case of hypocalcified AI rehabilitated with 28 ceramic metal-free…”
Section: Prosthodontic Proceduresmentioning
confidence: 99%
“…Only a few cases of DGI‐II treatment during the period of early mixed dentition were described in the literature 21,22 …”
Section: Discussionmentioning
confidence: 99%
“…According to the American Academy of Pediatric Dentistry (AAPD) Guideline (2017), in “severe cases with significant enamel fracturing and rapid dental wear, the treatment of choice is full coverage restorations in both the primary and permanent dentitions.” 14 Moreover, the patient's teeth had Grade 3 of teeth wear according to TWES, and according to this classification, the restorative treatment is to be considered when grade 3 or 4 exists on the surfaces that are involved in occlusion/articulation 20,23 . Thus, based on the above and considering that abnormally formed tooth tissues were erased along the entire length, the use of indirect restoration methods with full coverage of the crown with metal‐ceramic 21 or indirect composite restorations 21 was proposed as the most rational treatment method. The technique of direct composite restorations for a period of mixed dentition was also proposed 24 .…”
Section: Discussionmentioning
confidence: 99%
“…W badaniach radiologicznych obserwuje się również charakterystyczny wygląd zębów zaraz po wyrznięciu, gdzie komory i kanały są bardzo szerokie. [11][12][13] Komora i kanały szybko jednak się bardziej skomplikowane i wymaga podejścia interdyscyplinarnego.…”
Section: Wstępunclassified